2012
DOI: 10.1136/vr.100316
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and long‐term outcome of juvenile epilepsy in 136 dogs

Abstract: The aetiology and outcome of dogs with juvenile-onset seizures were investigated. One hundred and thirty-six dogs whose first seizure occurred before the age of one year were investigated. One hundred and two dogs were diagnosed with idiopathic epilepsy (IE), 23 with symptomatic epilepsy (SE), nine with reactive seizures (RS) and two with probable symptomatic epilepsy (pSE). The outcome was known in 114 dogs; 37 per cent died or were euthanased as a consequence of seizures. The mean survival time of this popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 30 publications
7
57
0
1
Order By: Relevance
“…This result has previously been found in human epilepsy [37]. The number of epileptic dogs that experience cluster seizures varies between studies, with recent reports between 38% and 64% [20], [38]. The breed least likely to achieve remission in this study was the Border Collie, a breed previously demonstrated to have a higher level of cluster seizures than other breeds (84.6% affected) [20], with similar levels reported in other studies (e.g.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result has previously been found in human epilepsy [37]. The number of epileptic dogs that experience cluster seizures varies between studies, with recent reports between 38% and 64% [20], [38]. The breed least likely to achieve remission in this study was the Border Collie, a breed previously demonstrated to have a higher level of cluster seizures than other breeds (84.6% affected) [20], with similar levels reported in other studies (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Early age at seizure onset has been previously identified in children to be a predictor of pharmacoresistance [54]. In contrast, in a study of canine juvenile epilepsy (where the first seizure occurs before the age of one year), age at onset had no influence on survival outcome [20].…”
Section: Discussionmentioning
confidence: 90%
“…The temporal distribution of epileptic seizures is an important prognostic factor in IE, with dogs experiencing CS less likely to achieve remission (Packer et al, 2014), experiencing a decreased survival time (Arrol et al, 2012;Berendt et al, 2007;Monteiro et al, 2012;Saito et al, 2001) and an increased likelihood of euthanasia (Fredso et al, 2014) compared to dogs with single epileptic seizure episodes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Caution needs to be adopted in trying to compare the percentage of therapeutic success between different studies due to the extreme variability in terms of AEDs used, inclusion criteria and follow-up duration (Heynold and others 1997, Berendt and others 2007, Arrol and others 2012). Not many reports detail the seizure-free state at a specific follow-up end point (De Risio 2014a) and the recent revision of the definition of seizure-free state (Potschka and others 2015) prevents an effective comparison of their results with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%